40. SURVEY ON THE USE OF ANTIBIOTICS IN OUTPATIENT TREATMENT OF OTORHINOLARYNGOLOGY DISEASES AT THE DEPARTMENT OF EAR, NOSE AND THROAT, VINH UNIVERSITY OF MEDICINE HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2024)
Research objective: Survey the situation of antibiotic use in outpatient treatment ofotolaryngological diseases at the Department of Ear, Nose and Throat, Vinh Medical UniversityHospital in 2022.Research method: Retrospective study on outpatient prescriptions at the Ear-Nose-ThroatDepartment of Vinh Medical University Hospital from April 2022 to April 2023.Research results: The five most common ENT diseases in the study sample are pharyngitis(42.39%), rhinitis (23.91%), chronic sinusitis (14.6%), and tonsillitis (12.5%) and otitis media(6.53%). The highest rate of ENT diseases occurs in the age group 16-60 years old (65.76%). Thereare 16 antibiotics used, of which amoxicillin-clavulanate is used the most (40.76%); The lowest arecefaclor, rifamycin and tyrothricin (with a rate of 0.54%). There are five types of antibiotics to treatotitis media - azithromycin (41.67%); There are three types of antibiotics to treat chronic sinusitis -amoxicillin-clavulanate (92.6%); There are five types of antibiotics to treat rhinitis - amoxicillinclavulanate (81.82%); There are 12 types of antibiotics to treat sore throat - sultamicillin is used(25.64%); There are 12 types of antibiotics to treat tonsillitis: amoxicillin- sulbactam is the most usedantibiotic (17.37%). Single regimens account for the majority of treatment regimens (80.43%).Conclusion: The most used antibiotics are the beta-lactam group and penicillin antibiotics combinedwith beta-lactamase inhibitors. Single regimens make up the majority of treatment regimens.
Keywords: Antibiotics, outpatient treatment, otorhinolaryngology, prescription.